Ramadan tafsir of the glorious Qur’an goes virtual during Covid-19 lockdown in Nigeria - Abdullahi Muhammad Maigari; Uthman Abdullahi Abdul-Qadir; Muhammad Muslim Ibrahim; Mustapha Bashir (Islamic Communication Journal, 2020)
The researchers were motivated by the adoption of digital communication applications and social media platforms by some Islamic scholars in Nigeria to conduct annual Tafsir of the glorious Qur’an in Ramadan 2020 in the midst of coronavirus lockdown. The paper adopted Lull’s Gratification Theory for theoretical explanation of virtual interaction between the scholars who conducted the Tafsir from an isolated places and the audience who watched or listened from their homes in adherence to safety measures to stop the spread of the disease. Methodologically, the study adopted a cross-sectional research design and purposive sampling technique to elicit secondary data from the target participants. The study found that there is usage of digital medium of communication and interaction between Islamic clerics and their followers. This explains the flexibility of Islam to embrace development, adopt and adapt it in conformity with Islamic rules and regulations. The findings also show that Facebook, WhatsApp and Telegram are the most common internet based interactive platforms which Islamic scholars explored and disseminated their Tafsir virtual to the audience. The paper concludes that internet has enabled people not only to interact virtual but Tafsir and other forms of Islamic preaching can be conducted without co-presence of the preachers and the audience. The option of live streaming video on Facebook, WhatsApp and Telegram which consume a lot amount of data has enabled Muslim users to followed the Ramadan Tafsir from distant places.